An Alternative Approach to Future Diagnosis: Can Generalized Anxiety Disorder Be Distinguished From Major Depressive Disorder, Healthy People by Differentially Expressed lncRNAs in Peripheral Blood - Kong L; Zhang L (Neuropsychiatric Disease and Treatment)
Lingming Kong,1 Liang Zhang2 1Treatment & Prevention Center for Mental Disorder, No. 904th Hospital, Changzhou, Jiangsu, 213003, People’s Republic of China; 2Psychiatry Department, The 5th People’s Hospital of Luoyang, Luoyang, Henan, 471027, People’s Republic of ChinaCorrespondence: Lingming Kong, Treatment & Prevention Center for Mental Disorder, No. 904th Hospital, North Peace Road 55, Changzhou, Jiangsu, 213003, People’s Republic of China, Email lingmk123@163.comPurpose: Symptomatic diagnosis combined with unclear pathological mechanism and diverse etiology may increase misdiagnosis risk for generalized anxiety disorder (GAD) in the clinical setting. This study aimed to confirm the diagnostic value of aberrantly expressed long non-coding RNAs (lncRNAs) for GAD.Patients and Methods: Eighty sex- and age-matched patients with GAD and major depressive disorder (MDD) and healthy controls (HCs) were enrolled using a convenient sampling method. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to verify lncRNA expression levels in all participants, and a receiver operating characteristic (ROC) curve was used to test the accuracy of aberrantly expressed lncRNAs in differentiating health conditions.Results: ΔCt values of ENST00000505825, NONHSAG017299, NONHSAT078768, NONHSAT029028, NONHSAT101077, NONHSAT031726, TCONS_l2_00010607 in GAD patients were less than in HCs (P< 0.05 or 0.01). The total severity score of HAMA-14 and somatic anxiety scores were negatively correlated with ΔCt values of ENST00000505825, NONHSAG017299, NONHSAT078768, NONHSAT029028, NONHSAT101077, NONHSAT031726, ENST00000505825, TCONS_l2_00010607, and NONHSAT131696, and psychic anxiety scores were negatively associated with the ΔCt value of ENST00000505825 (P< 0.05 or 0.01). The AUC of the combined ROC curve between patients with GAD and healthy people was 0.810, with sensitivity and specificity of 0.825 and 0.762, respectively (P< 0.05 or 0.01). The AUC of the combined ROC curve between patients with GAD and MDD patients was 0.938, with sensitivity and specificity of 0.850 and 0.900, respectively (P< 0.05 or 0.01).Conclusion: ENST00000505825, NONHSAG017299, NONHSAT078768, NONHSAT029028, NONHSAT101077, NONHSAT031726, TCONS_l2_00010607, which may serve as biomarkers for the GAD diagnosis and differentiation between GAD and MDD, can improve the diagnostic accuracy and avoid misdiagnosis to a certain extent. It is also beneficial for personalized treatment of GAD.Keywords: long non-coding RNAs, differential diagnosis, peripheral blood mononuclear cell, biomarker, receiver operating characteristic